2017
DOI: 10.1038/s41598-017-03716-7
|View full text |Cite
|
Sign up to set email alerts
|

Looking to nature for a new concept in antimicrobial treatments: isoflavonoids from Cytisus striatus as antibiotic adjuvants against MRSA

Abstract: The spread of multidrug-resistant Staphylococcus aureus strains, including methicillin-resistant S. aureus (MRSA), has shortened the useful life of anti-staphylococcal drugs enormously. Two approaches can be followed to address this problem: screening various sources for new leads for antibiotics or finding ways to disable the resistance mechanisms to existing antibiotics. Plants are resistant to most microorganisms, but despite extensive efforts to identify metabolites that are responsible for this resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 61 publications
1
66
1
Order By: Relevance
“…Intermolecular interactions lead to changes in dipolar moment, solubility and stability in various types of media. Molecules can form clusters that give rise to synergistic effects, but this aspect has barely been discussed in recent studies . One case is the joint action of binary mixtures of aguerin B, cynaropicrin, grosheimin and 11,13‐dihydroxy‐8‐desoxygrosheimin (Fig.…”
Section: Future Trends and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermolecular interactions lead to changes in dipolar moment, solubility and stability in various types of media. Molecules can form clusters that give rise to synergistic effects, but this aspect has barely been discussed in recent studies . One case is the joint action of binary mixtures of aguerin B, cynaropicrin, grosheimin and 11,13‐dihydroxy‐8‐desoxygrosheimin (Fig.…”
Section: Future Trends and Prospectsmentioning
confidence: 99%
“…Molecules can form clusters that give rise to synergistic effects, but this aspect has barely been discussed in recent studies. 238 One case is the joint action of binary mixtures of aguerin B, cynaropicrin, grosheimin and 11,13-dihydroxy-8-desoxygrosheimin (Fig. 6b), which increase the inhibitory activity of each compound separately against wheat coleoptile.…”
Section: Keep the Ecosystem Study As Complex As You Canmentioning
confidence: 99%
“…It has been reported that flavones and catechins appear to be the most powerful antioxidants, preventing the effects of reactive oxygen species in the body (Nijveldt et al 2001 ; Panche et al 2016 ). There are numerous studies highlighting the broad range of biological activities of flavonoids, including antioxidant (D’Amelia et al 2018 ), anti-cancer (LeJeune et al 2015 ), antimicrobial (Abreu et al 2017 ; Solnier et al 2020 ), antiviral (Wang et al 1998 ), and anti-inflammatory (Catarino et al 2016 ) activities (Panche et al 2016 ).
Fig.
…”
Section: Flavonoids and Their Antiviral Potential Against Coronavirusmentioning
confidence: 99%
“…22 In the study mentioned above, Abreu et al identified plant extract compounds that could act as antibiotic adjuvants "showing their great potential for application in the clinical therapy of infections with antibiotic-resistant microorganisms such as MRSA." 20 A review by Chambers and Deleo noted CA MRSA has characteristics not found in HA MRSA. Tissue-destructive infections that include necrotizing fasciitis and fulminant, necrotizing pneumonia may be a result of CA MRSA genes that encode the virulence factor Panton-Valentine Leukocidin, which induces leukocyte destruction and tissue necrosis.…”
Section: Eos Against Methicillin-resistant Staphylococcus Aureusmentioning
confidence: 99%